Sharia as a New Culture System of Identity in the Post-Conflict Aceh, Indonesia - Mubarrak, Husni; Zikri, Awwaluz; Hanapi , Agustin; Munir, Badrul; Iskandar, Iskandar (Hukum Keluarga Islam IAIN LANGSA, 2024)
The research on Aceh in various fields has been conducted by many scholars so far. What is felt less of concern in academic studies is on current period of post-conflict Aceh after peace process between Free Aceh Movement and Indonesian Army since 2005. This article would like to discuss about contemporary situation, especially in the post-conflict Aceh, on what has been shifted dealing with socio-cultural in Acehnese society. However, it has been a big change and shifting within society in Aceh, particularly after sharia religious law stipulated as the main legal formal that is objected as social engineering. Why sharia is important to be studied here could be not separated from Aceh’s long history and its deep role of Islamization process to South East Asia. Beside it is used as an identity, sharia currently in Aceh has also chosen as the new culture system and as the way out of prolonged armed conflict in Aceh that has taken place for more than three decades (1976-2005). By using theory religion as a culture system, this article would like to discuss and analyze about how does sharia now in Aceh become a new culture system of identity that broadly changed Aceh and its society, not only in socio-cultural, but also any other dimensions of life in contemporary time. The findings show that sharia religious law which has been institutionalized and stipulated as the main legal formal is more being objected as social engineering projects for future oriented social transformation and being a new culture system of identity.